Association and Predictive Value Analysis for Resting Heart Rate and Diabetes Mellitus on Cardiovascular Autonomic Neuropathy in General Population - Zi-Hui Tang; Fangfang Zeng; Zhongtao Li; Linuo Zhou (Journal of Diabetes Research)
Background. The purpose of this study was to evaluate the predictive value of DM and resting HR on CAN in a large sample derived from a Chinese population. Materials and Methods. We conducted a large-scale, population-based, cross-sectional study to explore the relationships of CAN with DM and resting HR. A total of 387 subjects were diagnosed with CAN in our dataset. The associations of CAN with DM and resting HR were assessed by a multivariate logistic regression (MLR) analysis (using subjects without CAN as a reference group) after controlling for potential confounding factors. The area under the receiver-operating characteristic curve (AUC) was used to evaluate the predictive performance of resting HR and DM. Results. A tendency toward increased CAN prevalence with increasing resting HR was reported (P for trend <0.001). MLR analysis showed that DM and resting HR were very significantly and independently associated with CAN (P<0.001 for both). Resting HR alone or combined with DM (DM-HR) both strongly predicted CAN (AUC = 0.719, 95% CI 0.690–0.748 for resting HR and AUC = 0.738, 95% CI 0.710–0.766 for DM-HR). Conclusion. Our findings signify that resting HR and DM-HR have a high value in predicting CAN in the general population.